PELATIHAN HMI DAN PLC DI SMK PADA JURUSAN ELEKTRONIKA INDUSTRI - Dwisaputra, Indra; Pratiwi, Indah Riezky; Rindry, Yang Agita; Triami, Ghea; Kristianto, Mardinata Indra (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Automation control systems are pivotal in the advancement of Industry 4.0, especially within vocational school settings. Nevertheless, significant challenges arise due to the lack of adequate instructional tools, resulting in disparities among vocational schools across different regions. To address this issue, this study proposes the provision of trainer kits and the conduction of comprehensive training on Programmable Logic Controllers (PLC) and Human-Machine Interfaces (HMI) to bolster practical learning experiences. Moreover, the integration of the Problem-Based Learning (PBL) approach within vocational school curricula is deemed essential. The successful implementation of PBL at the Polman Negeri Babel campus serves as a model to be replicated among vocational school teachers, with the aim of enhancing student engagement and contributing to the development of basic technological solutions within the community.This community service initiative seeks to strengthen collaboration between vocational schools and higher vocational education institutions. The anticipated outcomes include the provision of instructional tools, such as trainer modules, and targeted training on PLC and HMI to facilitate practical learning. These efforts are intended to improve the competencies of both teachers and students in industrial automation control systems, thereby underscoring the critical role of higher vocational education institutions in the development of vocational schools. Evaluation of the initiative revealed high levels of perceived usefulness, with a rating of 92.5%, followed by the effectiveness of the delivery method at 86.88%, and the quality of training materials at 80.83%. These results highlight the significant impact and value of the provided training and resources.